Mechanically Derived Tissue Stromal Vascular Fraction Acts Anti-inflammatory on TNF Alpha-Stimulated Chondrocytes In Vitro - van Boxtel, Joeri; Vonk, Lucienne A.; Stevens, Hieronymus P.; van Dongen, Joris A. (Bioengineering (Basel), 2022)
Enzymatically isolated stromal vascular fraction (SVF) has already shown to be effective as a treatment for osteoarthritis (OA). Yet, the use of enzymes for clinical purpose is highly regulated in many countries. Mechanical preparation of SVF results in a tissue-like SVF (tSVF) containing intact cell–cell connections including extracellular matrix (ECM) and is therefore less regulated. The purpose of this study was to investigate the immunomodulatory and pro-regenerative effect of tSVF on TNFα-stimulated chondrocytes in vitro. tSVF was mechanically derived using the Fractionation of Adipose Tissue (FAT) procedure. Characterization of tSVF was performed, e.g., cellular composition based on CD marker expression, colony forming unit and differentiation capacity after enzymatic dissociation (from heron referred to as tSVF-derived cells). Different co-cultures of tSVF-derived cells and TNFα-stimulated chondrocytes were analysed based on the production of sulphated glycosaminoglycans and the anti-inflammatory response of chondrocytes. Characterization of tSVF-derived cells mainly contained ASCs, endothelial cells, leukocytes and supra-adventitial cells. tSVF-derived cells were able to form colonies and differentiate into multiple cell lineages. Co-cultures with chondrocytes resulted in a shift of the ratio between tSVF cells: chondrocytes, in favor of chondrocytes alone (p < 0.05), and IL-1β and COX2 gene expression was upregulated in TNFα-treated chondrocytes. After treatment with (a conditioned medium of) tSVF-derived cells, IL-1β and COX2 gene expression was significantly reduced (p < 0.01). These results suggest mechanically derived tSVF stimulates chondrocyte proliferation while preserving the function of chondrocytes. Moreover, tSVF suppresses TNFα-stimulated chondrocyte inflammation in vitro. This pro-regenerative and anti-inflammatory effect shows the potential of tSVF as a treatment for osteoarthritis.